2008
DOI: 10.1103/physrevd.77.126018
|View full text |Cite
|
Sign up to set email alerts
|

New open string solutions inAdS5

Abstract: We describe new solutions for open string moving in AdS 5 and ending in the boundary, namely dual to Wilson loops in N = 4 SYM theory. First we introduce an ansatz for Euclidean curves whose shape contains an arbitrary function. They are BPS and the dual surfaces can be found exactly.After an inversion they become closed Wilson loops whose expectation value is W = exp(− √ λ).After that we consider several Wilson loops for N = 4 SYM in a pp-wave metric and find the dual surfaces in an AdS 5 pp-wave background. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…On the other hand we also find that the on-shell action vanishes corresponding to the expectation value of the corresponding Wilson line < W >= 1. This is in complete agreement with the result presented in [22].…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…On the other hand we also find that the on-shell action vanishes corresponding to the expectation value of the corresponding Wilson line < W >= 1. This is in complete agreement with the result presented in [22].…”
Section: Introductionsupporting
confidence: 83%
“…Following [20] we consider D5-brane with Euclidean world-volume. Then we shown that the solutions of the equations of motion correspond to the solution found in the first part of the paper [22]. Further, when we evaluate the action on this solution we obtain regularized value of the action that corresponds to the Wilson line in level Π anti-symmetric representation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations